The impact of public relations strategies on taxpayer compliance levels in tax authorities. - Chingozho, Takawira T (Midlands State University, 2020)
This study examined the impact of Public Relations strategies employed by tax administrations on the level of tax compliance in SME‘s in Zimbabwe. The study sought to determine the extent to which the PR activities implemented in ZIMRA as the tax administration in Zimbabwe are assisting in improving the levels of tax compliance, the main areas of the study were establishing tax compliance levels, establishing how increasing media presence could also affect tax compliance and how tax education impacted on tax compliance levels. Theoretical and empirical literature were reviewed in line with these study objectives. Overall, the study was guided by the Press agentry model, public information model, two way asymmetrical model and two way symmetrical model as proposed by Grunig and Hunt. The study adopted a positivism philosophy to facilitate the use of quantitative techniques. The study adopted the deductive approach to understand the impact of Public Relations on the level of tax compliance in SME‘s in Zimbabwe. The target population and sample size were 650 and 242. Structured questionnaires designed using a 5-point Likert scale were self-administered to a number of SME‘s in Harare who were selected using simple random sampling and four Tax consultants were interviewed. Quantitative data was analyzed using SPSS. The study found out that most of that most of the SME‘s in Zimbabwe are not yet registered with ZIMRA and the reason being that the lack adequate knowledge on how they to go about the registration process. The study also found out that most of the corporate image of ZIMRA is not good and this is the major contributor to the low levels of tax compliance in the country. On tax education the programs were found out not to be effective as most of the respondents lacked adequate knowledge on the need to be tax compliant citizens and also on what the government uses the money they collect through taxation. The study also established that the press still plays a major role in the disbursement of vital information to the public, however it was realized that ZIMRA is not effectively using the media to transmit important information like policy changes as well as newly introduced products and services to the public. It was also realized that social media is increasingly playing a major role in information dissemination as a lot of people are now increasingly using the internet and the tax administration needed to increase their presence on these various social media platforms so as to increase their reach to the public. The study concluded that public relations is key in improving tax compliance and as such tax administrations need to increase their public relations vi | P a g e CHINGOZHO TAKAWIRA T R0723971R efforts. The research recommended that it was very important for tax administrations to improve their image to ensure acceptance in the public eye, there is also a need for tax administrations to increase their presence on various media platforms like the newspapers and electronic media platforms so as to increase accessibility of information by the public. Tax education was also suggested as a very important factor in improving tax compliance as most of the people lack adequate knowledge on the importance of being tax compliant citizens. The research then recommended the tax administration to engage with relevant authorities to ensure that tax education be incorporated into the curriculum both at basic and tertiary education so as to create a highly conscious society on taxation issues. It was also recommended that effective communication is also an important factor in improving tax compliance and the tax administration needed to create two way communication channels that would enable their public to reach out to them without a lot of challenges. The use of social media platforms was suggested as one of the best ways to expedite communication as they provide a chance for real time communication with the public but it would need ZIMRA to have experts manning the social media sites at all times to facilitate communication.